The bank and the principle of caution when paying the check - Benlatreche, Mouna (Journal of Human Sciences, 2023)
The banking business, including the fulfillment of the check, is important and dangerous at the same time: this is what justifies the expectation from banks, as professionals, of a high degree of caution in dealing with checks and in their fulfillment in particular, especially since the state is moving towards imposing dealing with means of payment, in order to direct the funds of the parallel market to the banks. In addition, the life of the bank depends on a very sensitive issue, which is the trust of the public: its mistakes, lapses and lack of precaution will lead to shocking customers and their reluctance to deal with it. Commitment to the principle of caution in the field of honoring checks, then, is not only a duty of the bank, but rather it is an urgent necessity in the face of competition, and in the face of the risk of reluctance to deposit funds with banks; This is what makes refining his commitment to the principle of precaution on the part of the law and the judiciary together and in a coordinated manner, a very important issue for the public and private interest.